VISIBILITY OF PRECURSORS OF THE GONOPODS IN A FRESHWATER CRAYFISH, ASTACUS LEPTODACTYLUS ESCHSCHOLTZ, 1823 (DECAPODA, ASTACIDAE) - Harlioglu, Muzaffer M. (Brill Academic Publishers, 2016)
Astacus leptodactylus Eschscholtz, 1823 is an important, marketable species of crustacean, consumed intensely as a luxury food in many countries. Because A. leptodactylus is less cannibalistic than other crayfish species, is more fecund, and has a fast growth rate, it is accepted as a considerably suitable crayfish for culturing in extensive pond systems. Information on the reproductive biology and anatomy of crayfish is important for developing suitable production methods. Sex recognition may also be essential in separating males and females in crayfish rearing (i.e., to prevent cannibalism, males grow faster than females). Although male reproductive system morphology and spermatophore formation in crayfish, including A. leptodactylus, have been studied in detail, this study is the first to demonstrate the visibility of precursors of the gonopods and, thus, the actual presence of gonopods, which of course determine the male sex, in a freshwater crayfish. The present study shows that the first signs of secondary sexual characters (i.e., precursors of the gonopods) can be distinguished in the form of small tubercles on the first abdominal somite in male stage 4 juveniles, and the gonopods themselves are distinguishable in male stage 5 juveniles in A. leptodactylus. In conclusion, sex differentiation in A. leptodactylus can be realized already in stage 4 juveniles. Further studies should be carried out on the presence and shape of precursors of gonopods in stage 4 and gonopods in stage 5 juveniles of species of astacid crayfish in order to facilitate solving taxonomic problems in the family Astacidae.
Keywords: Juvenile narrow-clawed crayfish; monosex; morphology; reproduction; sex differentiation